(untitled) (Medico Legal Update, 2020)
Background/Objectives: Many microorganisms reside in the oral cavity, and they are referred to as oral-resident bacteria. Oral microorganisms are an important cause of oral diseases, and as such, many studies have been conducted to control them. This study aimed to investigate the antimicrobial activity against S. intermedius and S. gordoii among the oral-resident bacteria using Coptischinensis, a natural extract. Method/Statistical Analysis: To investigate the antimicrobial activity of Coptischinensis, the clear-zone confirmation method using filter paper and colony-forming unit (CFU) was used to check the bacterial proliferation. As the concentration of Coptischinensis increased, the size of the clear zone also increased. As a result of the CFU, bacterial proliferation was not observed in the experimental group as compared to the control group. Findings: The results of this study proved the antimicrobial activity of Coptischinensis against the oral-resident bacteria S. intermedius and S. gordoii. The clear zone results showed that S. intermedius and S. gordoii were larger in size than the control group.CFU showed a large amount of colony in the control group but not exist colony in the experimental group.The result showed its potential as an antimicrobial agent applicable to oral-resident bacteria. Improvements/Applications: S. intermedius and S. gordoii bacteria found in the oral cavity showed antimicrobial effect on the extracts. Coptischinensis was confirmed to be a preventative and therapeutic agent of tooth decay. In conclusion, the possibility that it can be applied to various intraoral antibacterial products in the future.